Analisis Hasil Belajar Menggunakan Media Whatsapp di Masa Pandemi Covid-19 dan Pembelajaran Tatap Muka di SMP Negeri 4 Semarang - Dewi Sucifitriyani; Ani Rusilowati; Sunyoto Eko Nugroho (Departement of Mathematics Education, 2023)
This study aims to determine the use of online learning media and face-to-face learning both in the advantages and disadvantages and obstacles faced by teachers in learning. This research uses descriptive research methods with a quantitative approach. This sampling technique uses probability sampling techniques. The sample used was grade VII and VIII students totaling 131 students. The results showed 1) Student learning outcomes using the online learning method sum score of 10,075. 2) The advantages of online learning methods include flexible time and place, there are learning videos that can be accessed by students, and save quota, while the disadvantages are the availability of different networks in each place, students cannot socialize directly, and the lack of teacher supervision of learning outcomes. 3) Student learning outcomes using the face-to-face method have a sum score of 10,900. 4) The advantage of face-to-face learning is that it can directly supervise student learning outcomes, interaction between students occurs. While the drawback is the lack of facilities for interactive learning, students are required to be disciplined in arriving on time, and making students dependent. 5) The obstacle faced by teachers is limited internet quota, not all teachers are familiar with using WhatsApp.